2021
DOI: 10.3390/toxins13010060
|View full text |Cite
|
Sign up to set email alerts
|

A Neurotoxic Snake Venom without Phospholipase A2: Proteomics and Cross-Neutralization of the Venom from Senegalese Cobra, Naja senegalensis (Subgenus: Uraeus)

Abstract: The Senegalese cobra, Naja senegalensis, is a non-spitting cobra species newly erected from the Naja haje complex. Naja senegalensis causes neurotoxic envenomation in Western Africa but its venom properties remain underexplored. Applying a protein decomplexation proteomic approach, this study unveiled the unique complexity of the venom composition. Three-finger toxins constituted the major component, accounting for 75.91% of total venom proteins. Of these, cardiotoxin/cytotoxin (~53%) and alpha-neurotoxins (~2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 83 publications
(127 reference statements)
5
37
0
Order By: Relevance
“…[74], whereas information on the preclinical efficacy of some antivenoms against panel of medically significant African snake venoms is limited [7,75]. This current study assessed the preclinical neutralization efficacy of the polyvalent VINS Snake Venom Antiserum -African IHS (SVA-AIHS) against medically relevant snake venoms from Elapidae (Naja spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[74], whereas information on the preclinical efficacy of some antivenoms against panel of medically significant African snake venoms is limited [7,75]. This current study assessed the preclinical neutralization efficacy of the polyvalent VINS Snake Venom Antiserum -African IHS (SVA-AIHS) against medically relevant snake venoms from Elapidae (Naja spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous preclinical studies using VINS venom antiserum exhibited variations and inconsistency in neutralization capacity of the venom antiserum. This may be due to the differences in the source of venom used in the experiment, or with experimental protocol employed, especially, regarding the multiples of LD 50 used as a 'challenge dose' in the lethality experiments [75,79,80]. This assertion was supported by varying reports on the effectiveness of snake venom neutralization potency of VINS venom antiserum products as follows:Wong et al [75] study showed that VINS African Polyvalent Antivenom (VAPAV) was able to cross-neutralize the lethal effect of N. senegalensis (Senegalese cobra) which is a homologue of N. haje (Egyptian cobra).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For antivenom neutralization, the study was conducted as previously described in [ 125 ]. In brief, a challenge dose of venom at 2.5 times LD 50 dissolving in saline water was pre-incubated with various dilutions of antivenom (4 dilutions of antivenom tested, 15 μL, 35 μL, 75 μL and 100 μL) at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…This cast of molecules expands the possibilities of applying mass profiling to study important snake species whose venoms lack PLA 2 s, e.g. the African non-spitting cobras Naja annulifera [22], N. senegalensis [23], N. haje [24] and N. nivea [24].…”
Section: Introduction: Fundamentals Of Biological Mass Spectrometrymentioning
confidence: 99%